Lycofargesiines A–F, further Lycopodium alkaloids from the club moss Huperzia fargesii. (June 2019) - Xiong, Juan; Meng, Wei-Jia; Zhang, Hai-Yan; Zou, Yike; Wang, Wen-Xuan; Wang, Xin-Yi; Yang, Qi-Lian; Osman, Ezzat E.A.; Hu, Jin-Feng
Abstract: Six undescribed Lycopodium alkaloids (LAs) comprising four lycodine-type (lycofargesiines A–D), one lycopodine-type (lycofargesiine E), and a phlegmarine-type (lycofargesiine F), together with 16 known ones were isolated from the club moss Huperzia fargesii . Their structures and absolute configurations were determined by extensive spectroscopic methods, electronic circular dichroism (ECD) analysis, and density functional theory (DFT) calculations. (7 S, 8 R, 12 R, 13 R )-Lycofargesiine A is a rare naturally occurring LA possessing an exocyclic double bond between C-15 and C-16, with ring A being a rare 2, 3-dihyropyridone motif. Lycofargesiine D is an uncommon lycodine-type alkaloid featuring a unique N -acetylated tetrahydropyridinyl segment (ring A), whereas lycofargesiine F is the first phlegmarane-type LA bearing two nitrone moieties. In addition to the isolated huperzine A in this study, another two isolates (lycofargesiine C and 16-hydroxyhuperzine A) were also found to show inhibitory activities against acetylcholinesterase (AChE), with IC50 values of 8.63 and 5.18  μ M, respectively. Graphical abstract: Six (lycofargesiines A–F) undescribed Lycopodium alkaloids were isolated from Huperzia fargesii . Lycofargesiine C and 16-hydroxyhuperzine A showed anti-AChE activities.Image 1 Highlights: Six undescribed Lycopodium alkaloids (LAs) were isolated from Huperzia fargesii. Lycofargesiine A represents the first LA featuring an exocyclic Δ 15 double bond. N -Acetylated lycodine-type lycofargesiine D has a rare tetrahydropyridinyl motif. Lycofargesiine F is an unusual phlegmarane-type LA possessing two nitrone moieties. Lycofargesiine C and 16-hydroxyhuperzine A showed remarkable anti-AChE activities.